1989
DOI: 10.1073/pnas.86.10.3877
|View full text |Cite
|
Sign up to set email alerts
|

Active transport of gamma-aminobutyric acid and glycine into synaptic vesicles.

Abstract: Although y-aminobutyric acid (GABA) and glycine are recognized as major amino acid inhibitory neurotransmitters in the central nervous system, their storage is poorly understood. In this study we have characterized vesicular GABA and glycine uptakes in the cerebrum and spinal cord, respectively. We present evidence that GABA and glycine are each taken up into isolated synaptic vesicles in an ATPdependent manner and that the uptake is driven by an electrochemical proton gradient. Uptake for both amino acids exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(40 citation statements)
references
References 37 publications
3
36
1
Order By: Relevance
“…We reasonably assume that GABA transport is stoichiometrically coupled to H + efflux and therefore, that refilling of GABA into SVs occurs on the order of several tens of seconds. Although the kinetics that we report represents the time required to load ∼50% of vesicles (almost all recycling pool vesicles), the rate of GABA uptake into SVs estimated here in living synapses is substantially faster than that measured previously using isolated SVs in vitro (τ is approximately several minutes) (44). However, the rate of GABA uptake is much slower than that of glutamate uptake measured at calyx of the Held synapses, which occurs with τ = 7 s at 35°C (4).…”
Section: Discussioncontrasting
confidence: 52%
“…We reasonably assume that GABA transport is stoichiometrically coupled to H + efflux and therefore, that refilling of GABA into SVs occurs on the order of several tens of seconds. Although the kinetics that we report represents the time required to load ∼50% of vesicles (almost all recycling pool vesicles), the rate of GABA uptake into SVs estimated here in living synapses is substantially faster than that measured previously using isolated SVs in vitro (τ is approximately several minutes) (44). However, the rate of GABA uptake is much slower than that of glutamate uptake measured at calyx of the Held synapses, which occurs with τ = 7 s at 35°C (4).…”
Section: Discussioncontrasting
confidence: 52%
“…GABAergic inhibitory signaling occurs in the brain, whereas both GABAergic and glycinergic signaling occur primarily in spinal cord and brain stem. Like other neurotransmitters such as L-glutamate and acetylcholine, GABA and glycine are actively accumulated in synaptic vesicles through vesicular neurotransmitter transporters (3)(4)(5)(6)(7). Currently, only one type of transporter, SLC32A1, is known to be responsible for this process and is referred to as either vesicular GABA transporter or vesicular inhibitory amino acid transporter (VIAAT) (2,8,9).…”
Section: Essentially the Same Results Were Obtained With Glycine Anomentioning
confidence: 99%
“…Recent evidence has demonstrated that glutamate, GABA and glycine are actively taken up and stored in isolated synaptic vesicles [53,54]. The vesicular loading occurs exclusively for glutamate or GABA using purified cerebrum vesicles and for glycine using spinal cord synaptic vesicles.…”
Section: Release and Storage Of Glutamate And Gabamentioning
confidence: 99%